Pharmacognostical and antioxidant activity investigations on Vernonia anthelmintica Wild fruits - Dogra, Nittya K. (International Journal of Pharmaceutical & Biological Archive, 2018)
Vernonia anthelmintica Willd. (Asteraceae) is an annual herb used conventionally for the management of diabetes, fever, wound, malaria, cancer, acne and stomach disorder. As the plant is of ethno-pharmacological relevance and has been used in a number of polyherbal formulations, therefore, pharmacognostical studies were carried out to confirm the identity and quality of V. anthelmintica fruits. Also, the plant has been used as a remedial measure for skin ailments and oxidative stress also triggers skin ailments, therefore, antioxidant potential of the plant was explored using DPPH assay. Methanol extract of the plant showed maximum DPPH scavenging effect (90.4%) at a concentration of 90 Î¼g/ml, whereas the standard drug - ascorbic acid showed maximum DPPH scavenging effect (94.8%) at 40 Î¼g/ml.